1982
DOI: 10.1002/spe.4380120202
|View full text |Cite
|
Sign up to set email alerts
|

On the performance of COBOL programs in large vs. mini computers

Abstract: The comparative performance characteristics of COBOL programs in a small versus large computer systems are investigated. The vehicle consists of a set of synthetic benchmark COBOL programs, each measuring a particular aspect of COBOL computations, data manipulation, and inputloutput is made on both a large scale computer (IBM370/158) and a minicomputer (Texas Instruments TI980). Results of a number of such experiments are presented and comparisons made between results obtained from the two systems.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1984
1984
1989
1989

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…(z) Disk caching can yield very substantial benefits in performance, but can also degrade performance unless it is used with some understanding of the types of processing where it provides benefits. (3) The hardware cache is the only one that can be used in all circumstances with substantial performance benefits in sequential as well as random processing. It can reduce I/O wait times by two thirds in a wide range of applications.…”
Section: Discussionmentioning
confidence: 99%
“…(z) Disk caching can yield very substantial benefits in performance, but can also degrade performance unless it is used with some understanding of the types of processing where it provides benefits. (3) The hardware cache is the only one that can be used in all circumstances with substantial performance benefits in sequential as well as random processing. It can reduce I/O wait times by two thirds in a wide range of applications.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for the worsening factor as file size increases could be the slow seek times on the PC AT hard disk: Schoeffler and Pechura (2] have shown that, as files get larger, the average random access time also increases since more cylinder boundaries have to be crossed. The PC AT disk is at a distinct disadvantage when it comes to crossing cylinder boundaries: Average seek time is 52 ms on the PC AT disk versus 25 ms on the mainframe.…”
Section: Input/outputmentioning
confidence: 99%